Building a Greener Future: Sustainable Education and Employment Trends in the European Union - Alexandra-Nicoleta CIUCU (DURNOI); Camelia DELCEA; Livia Diana IANCU; Bianca CIBU (Communications of International Proceedings, 2023)
One of the current problems facing humanity concerns the lack of balance between the skills of young people and the needs of the market. Quality Education is debated in the second Sustainable Development Goal (SDG) and proposes equal and affordable access to education, as well as increasing the number of young people and adults who possess relevant skills to obtain decent jobs; while SDG 8 defines Decent Work and Economic Growth, which aims to reduce the number of young people who are not employed or do not follow an educational or training program, as well as the inequalities encountered at work and the creation of decent jobs. The purpose of the current research is to analyze the two pillars that can make this equilibrium possible through the lens of the SDGs addressed to them. In this sense, a cluster analysis was carried out to determine the common characteristics, as well as the obvious differences between the EU member states. Following this analysis, it was observed that the countries in the south of the EU register significantly lower values ​​regarding some of the six analyzed indicators compared to the other member states. The analysis conducted in this study can provide a valuable foundation for policymakers in the fields of education and employment as they formulate their decisions.
Keywords: sustainability; quality education; decent work; cluster analysis